Adolescent’s involvement in premarital sex: a professional view / Nur Amiera Zainuddin and Nurul Izzati Ghazali - Zainuddin, Nur Amiera; Ghazali, Nurul Izzati (2022)
Sexual activity that is done before marriage is known as premarital sexual intercourse, and it is both illegal and immoral in various cultures and religions. The incidence of this sexual behaviour among adolescents has reportedly been rising nationwide. The fact that certain individuals of Malaysian society still believe discussing sexuality is taboo has led to an increase in adolescents’ sexual behaviour that is hard to curb. This demonstrates that the society as a whole lack of awareness regarding this issue. This study was done to obtain the professional’s view regarding the adolescent’s involvement in premarital sex. Also, this study was conducted to study three objectives (i) To identify the characteristics of adolescent’s involvement in premarital sex; (ii) To determine the factors that influence the adolescent’s involvement towards the issues of premarital sex; and (iii) To explain the government’s current initiative that can be reformulated to overcome the issues of premarital sex among adolescents. This study used a qualitative survey which is in-depth interviews had been done to the 6 respondents chosen from professionals that have experiences in handling the adolescents that has been engaged in premarital sex. Based on the interviews conducted, the characteristics of adolescents involved in premarital sex has been identified. There were also several factors that encourage the adolescents to involve in premarital sex. Besides, there should be made some renewal towards the government’s current initiative in combating the issue of premarital sex among adolescents. As this study was only limited from the view of professionals, it is recommended that future study can highlight the views from the adolescents and other groups of society as well regarding this issue.